PERENCANAAN DAN PENGENDALIAN MATERIAL PADA PROYEK KONSTRUKSI PALU GRAND MALL - Utama, Anugerah; Asnudin, Andi; Labombang, Mastura (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2013)
Palu Grand Mall construction project is a large-scale construction projects that use different types of materials with large amounts. Therefore, the planning and control of the appropriate material to be very important. The purpose of this study was to determine how the   process of planning and control of material and to determine the size of the procurement quantity of material from the two methods of inventory control consists of methods Lot For Lot and Economic Ordering Quantity method that provides the most optimal total costs in construction projects Palu Grand Mall. The method used in this thesis is descriptive photograph and methods Material Requirement Planning (MRP) consist of methods Lot For Lot (L4L) and the Economic Ordering Quantity (EOQ). The results revealed that, in the process of planning and controlling materials on construction projects Palu Grand Mall is the starting material requirements planning, material selection and proceed with the selection of suppliers of materials. Once that is done the booking and purchase of materials. Then the material receipt and storage of materials. The last process in the release of material to the construction site. Planning material procurement inventory control method provides a theoretical optimum total cost of inventory is a combined method of EOQ method and method L4L. The measure of the quantity of material procurement is a 5066 D19 iron rod, iron rods Ø10 number 58 591, iron rods D22 number 6638, beam 5/7 number 415 m3, and multiplex sheet 2903 with a total cost of inventories of Rp3.488.366, -.   Keywords: material, process planning and control, MRP